2012
DOI: 10.1109/tse.2011.85
|View full text |Cite
|
Sign up to set email alerts
|

Formal Analysis of the Probability of Interaction Fault Detection Using Random Testing

Abstract: Abstract-Modern systems are becoming highly configurable to satisfy the varying needs of customers and users. Software product lines are hence becoming a common trend in software development to reduce cost by enabling systematic, large-scale reuse. However, high levels of configurability entail new challenges. Some faults might be revealed only if a particular combination of features is selected in the delivered products. But testing all combinations is usually not feasible in practice, due to their extremely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 33 publications
0
45
1
Order By: Relevance
“…Researches suggest that random testing performs better than a large class of testing strategies [11], [12]. Also, unlike most other random testing adaptations which do not use any information about the program or the specification [28], the adaptation in this work uses information on the test targets [13] derived from k-Reg models.…”
Section: Random(kþ þ1)mentioning
confidence: 99%
“…Researches suggest that random testing performs better than a large class of testing strategies [11], [12]. Also, unlike most other random testing adaptations which do not use any information about the program or the specification [28], the adaptation in this work uses information on the test targets [13] derived from k-Reg models.…”
Section: Random(kþ þ1)mentioning
confidence: 99%
“…Pure RT [14][15][16][17][18][19] Adaptive RT [20][21][22][23][24] Recent advances in random testing (2010)(2011)(2012)(2013)(2014) Guided RT [25][26][27][28] Fuzz testing [29][30][31] …”
Section: Random Testingmentioning
confidence: 99%
“…A study with 13 container classes showed that RT and Shape Abstraction [103] achieve similar predicate coverage and mutation score, but RT is significantly less expensive than Shape Abstraction [17]. Another recent study compared RT to CIT techniques (see Section 6) demonstrating that RT can be preferable to CIT in many circumstances [19].…”
Section: Pure Random Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…When interactions are to be examined, testing involves a combination-based strategy Grindal et al (2005a). Random testing (see Arcuri and Briand (2012) Bryce et al (2011).…”
mentioning
confidence: 99%